Juridical Analysis Juridical Analysis Of The Legal Protection Of Children With Special Needs In Inclusive Education - Diniati, Siti; Abdillah, Junaidi (Dinasti Research, 2025)
Inclusive education is a strategic policy to ensure the right to education for all children, including those with special needs. However, despite Indonesia’s strong normative framework supporting inclusive education, implementation remains uneven. This paper aims to examine the effectiveness of legal protection for children with special needs within the inclusive education system, using SMA Negeri 3 Pangkalpinang as a case study. The study employs an empirical juridical method, combining normative legal analysis with field observations and interviews involving educators, parents, and school administrators. The findings reveal a significant gap between the legal framework and the real conditions in schools. Key challenges include the absence of certified special assistant teachers, inadequate inclusive facilities, and limited awareness among stakeholders. The study concludes that while legal guarantees exist, systemic implementation barriers hinder their realization. Strengthening inclusive education requires harmonized policies, structural support, and a shift in legal culture within school communities.